Cardiac output in athletes - Ekblom B.; Hermansen, L. (Journal of Applied Physiology, 1968)
Cardiac output (dye-dilution technique) was determined during submaximal and maximal treadmill exercise on eight well-trained top athletes with very high maximal oxygen uptake (average value 5.57 liters/min or 73.9 ml/kgper min). Cardiac output and stroke volume averaged 36.0 liters/min and 189 ml, respectively. The highest individual values were 6.24 liters/min (81.1 ml/kg per min) for oxygen uptake and 42.3 liters/min for cardiac output. Owing to a relatively low arterial oxygen content (mean hemoglobin concentration 14.3 g/100 ml of blood) during maximal exercise, the maximal arteriovenous oxygen difference averaged only 156 ml/liter.